In vitro Antifungal Evaluation and Studies on the Mode of Action of Xanthoxyline Derivatives - Pinheiro, Taˆnia R; Yunesa, Rosendo A; L´pez, Silvia N; Santecchia, Carina B.; Zacchino, Susana AS; Filho, V Cechinel (Arzneimittelforschung, 1999)
This study describes the fungistatic effect of xanthoxyline (CAS 90-24-4) and its derivatives against a panel of yeasts, filamentous fungi and dermatophytes, by using the agar dilution method. Results indicated that simple structural modifications led to more potent derivatives, especially in relation with dermatophytes. The most active compound tested (10), which is a benzenesulphonyl derivative, was 12-fold more potent than xanthoxyline itself against Tricho- phyton rubrum. The evaluation of the mode of action with the whole cell Neurospora crassa assay, suggested that some selected compounds may be acting by the inhibition of fungal cell-wall polymers synthesis or assembly.
Keywords: Antifungal drugs; Dermatophytes; Xanthoxyline derivatives; antifungal activity, mode of action, synthesis